Translation Techniques of Affect on Riley’s Utterances In The Movie “Inside Out 2”: Appraisal Perspective - Muliawati, Silvia Dwina; Cahyono, Setyo Prasiyanto (Universitas PGRI Semarang, 2025)
The aims of this study are to find out the feelings and emotions expressed by Riley as the main character in the “Inside Out 2” movie and to explore the translation techniques used to translate the emotions that convey the main character's feelings. This study utilizes a descriptive qualitative method and the data were collected by using purposive sampling. The data were analyzed by applying Molina and Albir's (2002) translation techniques framework and Martin and White's (2005) appraisal framework. The result of this study shows that In/Security is the most common type of affect found in the data with 36 data because the feelings expressed by the main character show that growing up and getting puberty can make the main character feel anxious, Un/Happiness with 35 data, Dis/Satisfaction with 28 data and Dis/Inclination with 9 data simultaneously. Besides that, the translation technique frequently used is Established Equivalent with 34 data because the translator wants to make it easier for the readers to understand the message of feelings correctly by translating the SL as an equivalent into the TL, Reduction with 22 data, Literal Translation with 18 data, and Modulation with 17 data, Adaptation with 7 data, and Transposition with 6 data, Borrowing with 2 data, Linguistic Compression with 2 data, Generalization with 1 data respectively. The most common translation technique used is Established Equivalent because the translator has to determine the appropriate translation technique in transferring the meaning to TL.